Performance Analysis of Working Fluids on Organic Ranking Cycle Using Waste Heat from Flue Gas - Wahyu Nur Fadilah; Kartika Meylia Putri; Joke Pratilastiarso (ROTASI, 2023)
The increasing in electricity demand was inversely proportional to the supply of fossil fuels. It required various parties to find innovations to produce more electrical energy without increasing the use of fossil fuels. Organic Rankine Cycle (ORC) was one of the ways to generate electricity with a low heat source and it was affected by the type of refrigerant used as a working fluid. Therefore, this research was conducted to find a working fluid that produced good thermal efficiency and power for the ORC system by utilizing the flue gas from the steam power plant. Simulations were carried out using CoolProp software to determine the properties of the working fluid to be used and Cycle Tempo software to simulate the ORC system. This study used variations of working fluid R134a, R404A, R407C, R410A, and R507. In addition, flowrate variations of 100 kg/s, 150 kg/s, 200 kg/s, 250 kg/s, and 300 kg/s were also used. From this research, the highest thermal efficiency occurred at a flowrate of 300 kg/s using a working fluid R407C, it was 36.19%. The largest net power was also obtained at a flow rate of 300 kg/s using the working fluid R407C, it was 26980.9 kW.